2019
DOI: 10.1177/1748006x19867776
|View full text |Cite
|
Sign up to set email alerts
|

A domain adaptation model for early gear pitting fault diagnosis based on deep transfer learning network

Abstract: In recent years, research on gear pitting fault diagnosis has been conducted. Most of the research has focused on feature extraction and feature selection process, and diagnostic models are only suitable for one working condition. To diagnose early gear pitting faults under multiple working conditions, this article proposes to develop a domain adaptation diagnostic model–based improved deep neural network and transfer learning with raw vibration signals. A particle swarm optimization algorithm and L2 regulariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…e basic energy function used in the experiment is Tversky loss, as shown in equation (8), and β � 0.7 is set in this experiment:…”
Section: Experimental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…e basic energy function used in the experiment is Tversky loss, as shown in equation (8), and β � 0.7 is set in this experiment:…”
Section: Experimental Analysismentioning
confidence: 99%
“…The main clinical treatment of these diseases is the use of drugs and stereotactic neurosurgery. With the development and combined application of stereotactic technology, computer technology, and imaging technology, stereotactic surgery has gradually become the main means for the treatment of such neurological diseases [ 8 ]. Lancelot et al proposed that the common target area in clinical DBS surgery is located in the deep nucleus of the brain, among which a key common site is the thalamus.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the learning model may not yield correct labels for the unlabeled target domain and may diagnose the damage improperly for the target structure. From the domain adaptation perspective, the distribution shift between source and target domain should be addressed (Singh, Azamfar, Ainapure, & Lee, 2020;J. Li, Li, He, & Qu, 2020).…”
Section: Domain Adaptation In Shmmentioning
confidence: 99%
“…Besides, more expressive features can be extracted automatically by deep transfer learning and it utilizes the self-extraction of deep learning together with transfer learning to acquire "new knowledge", which assist to solve small sample data problem well in few-shot learning [11]. This learning method is commonly used for mechanical fault diagnosis [12][13][14][15][16]. For example, Zhao et al [17] reported a transfer learning framework based on the deep multi-scale convolutional neural network.…”
Section: Introductionmentioning
confidence: 99%